Características do carbono orgânico dissolvido e do bacterioplâncton da planície de inundação do alto rio Paraná. - Teixeira, Mariana Carolina (2010)
Since the introduction of the Microbial Loop concept, many studies aimed to explain the role of bacterioplankton and dissolved organic carbon (DOC) in aquatic ecosystems. Paraná River floodplain system is a very complex environment where these subjects were little explored. UV-VIS and fluorescence spectroscopy were utilized to identify DOC main source in six environments of the Upper Paraná River floodplain, where bacterioplankton communities were also characterized in terms of biomass, biovolume and density. The samples were obtained from November 2007 to September 2008. In general, the results showed that autochthonous sources of DOC are more important in the environments connected with Paraná River. In Patos, Ventura, Fechada and Guaraná lagoons, allochthonous DOC was more important, but in some periods DOC from primary production can gain importance, considering that chlorophyll could be related to a variation in spectroscopic indexes. Bacterial community, in relation to density, biomass and biovolume, is similar to those from other freshwater environments and both density and biomass were higher in the period with less rain. The limnological variables and spectroscopic features that were related with bacterioplankton were temperature, total nitrogen, total phosphorous, phosphate, transparency, conductivity and humification degree. The analysis of these relations indicated a possible competition between phytoplankton and bacterioplankton and also the utilization of labile carbon from aquatic macrophytes decomposition by bacterioplankton.